2022
DOI: 10.2147/jir.s365611
|View full text |Cite
|
Sign up to set email alerts
|

The Beneficial Effects of Hydrogen-Rich Saline Irrigation on Chronic Rhinitis: A Randomized, Double-Blind Clinical Trial

Abstract: Purpose Chronic rhinitis (CR) is a common chronic inflammation of the nasal mucosa. Nasal saline irrigation has been demonstrated to be an effective treatment for CR. In this study, we investigated the beneficial effects of hydrogen-rich saline irrigation as an anti-inflammatory irrigation therapy for CR and compared its effectiveness over saline irrigation. Hydrogen-rich saline (HRS) was investigated due to its antioxidant and anti-inflammatory properties. Methods A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Subgroup analysis found that AR patients had more significant treatment effects, so it is believed that HRS can be effectively used in the clinical treatment of CR patients. 56 There are also clinical studies on other AR treatment methods, such as a 2021 meta-analysis that summarized 56 clinical studies on "phototherapy" for AR. 57 Although this therapy has a positive effect on AR, there are still shortcomings such as a small sample size, lack of summary on long-term side effects, and a high risk of research bias.…”
Section: Hydrogen In Clinical Research On Improving Nasal Mucosal Inf...mentioning
confidence: 99%
See 2 more Smart Citations
“…Subgroup analysis found that AR patients had more significant treatment effects, so it is believed that HRS can be effectively used in the clinical treatment of CR patients. 56 There are also clinical studies on other AR treatment methods, such as a 2021 meta-analysis that summarized 56 clinical studies on "phototherapy" for AR. 57 Although this therapy has a positive effect on AR, there are still shortcomings such as a small sample size, lack of summary on long-term side effects, and a high risk of research bias.…”
Section: Hydrogen In Clinical Research On Improving Nasal Mucosal Inf...mentioning
confidence: 99%
“…Jin et al 56 conducted a pilot study on a small sample of AR patients and found that hydrogen-rich normal saline nasal irrigation can significantly improve the nasal mucosal physiological function of AR patients. Based on this, the sample size was further expanded, and a total of 120 CR patients, including AR and NAR, were randomly divided into two groups, hydrogen-rich normal saline group and normal saline group, for a double-blind controlled study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, there have been basic studies on the use of hydrogen-rich saline to improve chronic inflammation in the nasal mucosa, and it was found that hydrogen-rich saline achieved antioxidant effects by directly neutralizing free radicals and indirectly increasing superoxide dismutase levels [ 79 ], and also reduced the transcription and expression of inflammatory factors IL-4 and IL-13 in the nasal mucosa of experimental guinea pigs, reducing inflammation and promoting the recovery of nasal mucosa physiological functions [ 80 ]. On this basis, clinical studies have been conducted on the use of hydrogen-rich saline for chronic rhinitis [ 81 ] and CRS, with the hope that it will become another effective alternative to NI for CRS.…”
Section: Studies Related To the Composition Of Nasal Rinse Solutionmentioning
confidence: 99%
“…11 Non-allergic rhinitis and allergic rhinitis exhibited comparable levels of ECP and other inflammatory biomarkers. 12 Recombinant Keratin 5 (KRT5), also recognized as Cytokeratins 5 (CK5), is expressed in a highly specific manner in epithelial cells where it plays a crucial role in the integrity and mechanical stability of the cells. 13 Epithelial dysfunction in NPs exhibits some morphological changes, including squamous metaplasia, basal cell proliferation, goblet cell hyperplasia and the loss of differentiation of ciliated cells.…”
Section: Introductionmentioning
confidence: 99%